Perilaku Pemandu Wisata Lokal di Desa Wisata Bagot Kabupaten Samosir - Marciella Elyanta (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
Bagot Tourism Village is one of the tourism villages in Samosir Regency which has an attraction in the form of Batak and bagot culinary specialties. As one of the tourist attractions visited by many tourists, quality services must be carried out by local tour guides. However, the quality of human resources, especially the behavior of members of Pokdarwis Bagot Tourism Village as tour guides in serving tourists, still needs attention. The purpose of this study was to determine the behavior and appearance of local tour guides in the Bagot Tourism Village, Samosir Regency. The research method used is a qualitative research method with data collection techniques in the form of observation and interviews. The results of this study are the behavior of local tour guides in Bagot Tourism Village, Samosir Regency in serving tourists is quite good. However, there are also shortcomings in terms of acting quickly and decisively to overcome problems that arise in scouting. The appearance of the local tour guide in Bagot Tourism Village, Samosir Regency, has a pretty good appearance when on duty, such as in terms of hair, face, other body parts, and clothes. However, there are still shortcomings in terms of appearance, such as the hair of female tour guides is always in a ponytail, the face of local male tour guides is still mustache, and in terms of clothing they do not use identification and uniforms.